Analytical and numerical assessment of a preliminary support design – a case study. Issue 1 (1st January 2021) - Sebbeh-Newton, Sylvanus; Abdulazeez Shehu, Shaib; Ayawah, Prosper; Kaba, Azupuri A.; Zabidi, Hareyani
Abstract: Underground tunneling results in redistribution of the in-situ stress state. This process can create unstable underground conditions. Tunnel instability can result in fatalities, property damages, project delays, high rehabilitation cost, and can compromise the overall functionality of the excavation. This study assesses the efficiency of the empirically recommended support design of the Pahang-Selangor Water Transfer Tunnel in Peninsular, Malaysia using convergence-confinement (CV-CF) and 2-Dimensional two-dimensional Finite Element Method (FEM). To reduce the effect of subjective uncertainties associated with the rock mass rating system, the lump rating system was replaced with the continuous rating system to classify the rock masses and provide empirical support design for the tunnel. The maximum capacity and stiffness of the support systems were analytically determined using the CV-CF method. The results of the maximum elastic deformation of the support systems were compared to the actual critical internal pressures which show that the empirically recommended support systems can satisfactorily stabilize the underground excavation. The Reliability of the support design, the plastic zones, and total deformations were determined using Phase 2 . The radius of plastic zones and the maximum total deformations were significantly reduced after the supports were installed. The plastic zones that remained were restricted within the reinforced zones, signifying the effectiveness of the recommended support systems.